A 3rd serving of chicken soup for the soul : 101 more stories to open the heart and rekindle the spirit - Canfield, Jack, 1944-; Hansen, Mark Victor (Deerfield Beach, Florida : Health Communications, 1996)
A collection of 101 stories that provide examples of human beings at their best and share inspirational lessons on love, parenting, teaching, learning, death, attitude, and overcoming obstacles.
Adult.
Adult
Keywords: Spiritual life -- Anecdotes; Spiritual life -- Anecdotes